Międzynarodowa edukacja teatralna na przykładzie polsko-francuskich projektów artystycznych „Szekspir Projekt” i „MOON” - Anna Krzemińska (Annales Universitatis Paedagogicae Cracoviensis. Studia de Cultura, 2019)
The article discusses the issue of theatre education with the use of circus art elements in workshops for youth in the intergenerational and international context. Using as examples two Polish-French projects named „Shakespeare Project” and „MOON”, whose aim was an artistic exchange between professional French actors and a group of young circus artists from Klub 303 Ośrodka Kultury Kraków–Nowa Huta, the author presents multidimensional (educational, social and intercultural) influence of theatre.